^{164}Pb: A possible heaviest N=Z doubly magic nucleus - Tomoya Naito (内藤智也); Masaaki Kimura (木村真明); Masaki Sasano (笹野匡紀) (Physical Review Research)
We confirm by using the Skyrme Hartree-Fock-Bogoliubov calculation that ^{164}Pb is a possible heaviest N=Z doubly magic nucleus whose lifetime is long enough to be measured on accelerator experiments. We estimate the proton-emission and alpha-decay half-lives of ^{164}Pb. The estimated proton-emission half-life ranges from 0.1ps to 10ns, while the alpha decay can be safely neglected.